Oral Health Evaluation in Children with Special needs- A Retrospective Study - SRIRAM, KADAMBARI; JESSY P; SANTHOSH KUMAR M P (The journal of contemporary issues in business and government, 2020)
Special needs children primarily refer to children whose physical or intellectual capacities have been affected to a certain degree. Oral diseases can be considered as a public health due to their high rate of prevalence and significant social impact. While oral problems considerably affect the general health status of normal children, children with special needs are at significantly higher risk. There is limited literature regarding the oral health status of children with special needs in the area under study.The aim of the study was to evaluate the oral health among pediatric patients with special needs in a Dental Hospital. A retrospective study was carried out using case records of patients who reported to the Department of Paediatric and Preventive Dentistry from June 2019 to March 2020. A total of 29 children with special needs were included for the study after considering the inclusion criteria. The age, gender,Simplified Oral Hygiene index scores,Gingival index scores,DMFT scores and Plaque index scores were observed from the case records and tabulated on a spreadsheet.The collected data was analysed by SPSS software version 20.0. The level of significance set at p<0.05.Chi-square test was used to compare the gender wise and age wise oral status of the patients. It was observed that significant association between gender and caries incidence (p<0.05). Within the limits of the study, it can be concluded that oral health in special children has an significant association with gender in regard to caries incidence.Males had poor oral hygiene with higher plaque and gingival scores. In regard to age 8 to 12 year and 13 to 17 year children had poor oral hygiene with high plaque and gingival scores. A preventive dentistry program should be undertaken in future involving parents, teachers, and specialized dental teams to look after the oral health needs of the disabled population.